Physics Teaching Materials Based on The Creative Problem-Solving Model with Concept Maps: The Effect on Students’ Learning Outcomes - Vinna Natasya Putri; Putri Dwi Sundari; Hufri Hufri; Silvi Yulia Sari (Jurnal Penelitian Pendidikan IPA, 2024)
This motivation research is the low learning outcomes of physics students at SMA Pertiwi 1 Padang. The process of learning es the teacher does not activate students in finding solutions to problems in elasticity and static fluid material and the materials for teaching used that do not support the model of learning chosen by the teacher. The research type conducted was a quasi experiment using the Randomized Posttest Only Control Group Design. Purposive Sampling was used as a technique. Around 37 and 34 students involved in this study as experiment and class for control respectively. Data obtained from a test with multiple choice questions. Based on data analysis, the average physics outcomes of learning from students in the knowledge aspect in the in class for experimental is 82 which higher than the class for control which is 76. Hypothesis testing of the posttest conducted tc  tt where 1.831  1.666 H0 is rejected and H1 is accepted, the conclusion is the research results that the use of physics material for teaching based on the creative problem-solving model with concept maps has a effect in significant on the outcomes of learning from students in class XI MIPA SMA Pertiwi 1 Padang on the knowledge aspect with a real level of 0.05.